Manganese Dioxide Nanoparticles Prepared by Laser Ablation as Materials with Interesting Electronic, Electrochemical, and Disinfecting Properties in Both Colloidal Suspensions and Deposited on Fluorine-Doped Tin Oxide (2022)
ABSTRACT: Nanoparticles (NPs) of α-MnO2 have high applicability in photoelectrochemical, heterogeneous photocatalysis, optical switching, and disinfection processes. To widen this panorama about MnO2 NPs, the formation of this material by laser ablation and deposition by dip-coating on fluorine-doped tin oxide (FTO), were considered in this study. The optical, spectroscopic, electrochemical characterization, and the evaluation of the antimicrobial activity, plus the photocatalytic response, were measured herein in colloidal media and deposited. For the deposition of NPs on FTO sheet, an anode is produced with a pseudocapacitive behavior, and 2.82 eV of band gap (GAP) in comparison with colloidal NPs for a value of 3.84 eV. Both colloidal suspension and deposited NPs have intrinsic antibacterial activity against two representative microorganisms (E. coli and S. aureus), and this biological activity was significantly enhanced in the presence of UVA light, indicating photocatalytic activity of the material. Thus, both the colloidal suspension and deposited NPs can act as disinfecting agents themselves or via light activation. However, an antibacterial behavior different for E. coli and S. aureus was observed, in function of the aggregation state, obtaining total E. coli disinfection at 30 min for deposited samples on FTO.